The Influence of Social Media Content on Tourists' Stay Intention in Nature-Based Accommodation: A Study of Glamping - Ni Kadek Sri Mirayani; I Gusti Ngurah Oka Widjaya; Ni Putu Ariningsih; Ni Wayan Gita Sadhana Savitri; Desak Made Purnama Dewi (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
This study aims to analyze the influence of social media content on tourists' stay intention in nature-based accommodation, using glamping as the study context. The study employed an explanatory quantitative design through an online survey of 125 respondents who had seen glamping content, promotions, reviews, or recommendations on social media. Social media content was measured through five dimensions: information clarity, credibility, visual attractiveness, interactivity, and user reviews; while stay intention was measured through interest, consideration as an accommodation option, information search, booking intention, and willingness to choose glamping. The analysis shows that the instruments were reliable, with Cronbach alpha values of 0.957 for social media content and 0.870 for stay intention. Pearson correlation indicates a very strong positive relationship between social media content and stay intention (r = 0.881; p < 0.001). Simple linear regression shows that social media content has a positive and significant influence on stay intention (B = 0.945; p < 0.001), with R2 = 0.777. These findings confirm that informative, visual, interactive, credible content strengthened by e-WOM can shape tourists preferences for glamping experiences.